Regulating retrotransposon activity through the use of alternative transcription start sites. (22nd February 2016) - Persson, Jenna; Steglich, Babett; Smialowska, Agata; Boyd, Mette; Bornholdt, Jette; Andersson, Robin; Schurra, Catherine; Arcangioli, Benoit; Sandelin, Albin; Nielsen, Olaf; Ekwall, Karl
Abstract: Retrotransposons, the ancestors of retroviruses, have the potential for gene disruption and genomic takeover if not kept in check. Paradoxically, although host cells repress these elements by multiple mechanisms, they are transcribed and are even activated under stress conditions. Here, we describe a new mechanism of retrotransposon regulation through transcription start site (TSS) selection by altered nucleosome occupancy. We show that Fun30 chromatin remodelers cooperate to maintain a high level of nucleosome occupancy at retrotransposon‐flanking long terminal repeat (LTR) elements. This enforces the use of a downstream TSS and the production of a truncated RNA incapable of reverse transcription and retrotransposition. However, in stressed cells, nucleosome occupancy at LTR elements is reduced, and the TSS shifts to allow for productive transcription. We propose that controlled retrotransposon transcription from a nonproductive TSS allows for rapid stress‐induced activation, while preventing uncontrolled transposon activity in the genome. Synopsis: Retrotransposons can be activated under cellular stress conditions or at specific developmental stages. This study reveals a new mechanism of dynamic retrotransposon regulation by alternative transcription start site (TSS) selection. Fun30 chromatin remodelers maintain a critical nucleosome in LTR elements leading to the usage of a downstream TSS and the production of RNA incapable of reverse transcription and retrotransposition. In stressed cells, or in Fun30 mutants, the LTR nucleosome occupancy is reduced and the TSS shifts to allow for productive transcription and retrotransposition. Abstract : Retrotransposons can be activated under cellular stress conditions or at specific developmental stages. This study reveals a new mechanism of dynamic retrotransposon regulation by alternative transcription start site (TSS) selection.